Bilateral idiopathic granulomatous mastitis a rare benign inflammatory disease of breast: case report - Hussain, Talib; Bhardwaj, Subash (International Journal of Research in Medical Sciences, 2019)
Idiopathic Granulomatous Mastitis (IGM) is an uncommon benign inflammatory disorder of breast. Peri-ductal mastitis is thought to be the initial inflicting factor for its development. IGM usually presents as painful swelling, abscess or sinus/fistula in breast. There are no specific findings on ultrasound or mammographic imaging, and moreover it looks BIRADS-IV on mammography. Histopathology provides the final diagnosis. Here authors report a case of bilateral IGM which was successfully treated with surgery.